2019
DOI: 10.1038/s41598-019-41712-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype Genetic Variant in PER2 is Associated with Intrinsic Circadian Period in Humans

Abstract: The PERIOD2 ( PER2 ) gene is a core molecular component of the circadian clock and plays an important role in the generation and maintenance of daily rhythms. Rs35333999, a missense variant of PER2 common in European populations, has been shown to associate with later chronotype. Chronotype relates to the timing of biological and behavioral activities, including when we sleep, eat, and exercise, and later chronotype is associated with longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Human Per2 is present on chromosome number 2 [14], to be precise on 2q37.3 [15]. Per2 is one of the circadian pacemaker [15] that plays an important role in circadian time keeping in humans [27]. Per2 is a positive regulator of circadian gene expression [11,16,21] but possibly delays the clock [11,23].…”
Section: Per2 Genementioning
confidence: 99%
“…Human Per2 is present on chromosome number 2 [14], to be precise on 2q37.3 [15]. Per2 is one of the circadian pacemaker [15] that plays an important role in circadian time keeping in humans [27]. Per2 is a positive regulator of circadian gene expression [11,16,21] but possibly delays the clock [11,23].…”
Section: Per2 Genementioning
confidence: 99%
“…A length polymorphism in the PER3 gene due to a variable-number tandem repeat (4 or 5 repeats) has been linked to DSP in which the longer allele is associated with morningness and the shorter allele with eveningness [50]. A missense PER2 variant, Rs35333999, is associated with longer circadian period and later chronotype [40,51]. A single mutation in the CRY1 gene, CRY1 c.1657 + 3 A > C, has been identified that confers an autosomal dominant DSP trait [52].…”
Section: Gwas Of Chronotypementioning
confidence: 99%
“…It is a key clock gene that regulates circadian rhythms of mammals on the level of pathology, physiology and gene expression. 7 Interruption in the expression of PER2 can lead to reduction in the transcription level of other clock genes. 8 In addition, a previous study which has also shown an interaction between PER2 and inflammation cytokine, shows the expression of PER2 reduced in synchronized fibroblasts after TNF-a treatment.…”
Section: Introductionmentioning
confidence: 99%